Behavior and cuticular hydrocarbons of myrmecophilous insects (coleoptera: staphylinidae; diptera: phoridae; thysanura) associated with Asian aenictus army ants (hymenoptera; formicidae) - Hashim, Rosli; Komatsu, T.; Maruyama, M.; Akino, T. (2009)
Thirteen species of myrmecophilous insects belonging to three orders associated with three species of Aenictus ants (Aenictus laeviceps, Aenictus gracilis,,Aenictus sp. 18a of SKY) were studied for behavioral observation and cuticular hydrocarbon (CHC) analysis. The myrmecophiles are: Aenictobia thoi, Aenictobia fergusoni, Mimaenictus wilsoni, Aenictoteras malayensis, Rosciszewskia gracilis, Trichotobia gracilis, Aenictoxenus sp., Weissflogia rhopalogaster (Coleoptera: Staphylinidae, rove beetles); Dohrniphora kistneri, Dohrniphora sp. 1, Dohrniphora sp. 2, Vestigipoda maschwitzi (Diptera: Phoridae, scuttle flies); Thysanura fam. gen. sp. (Thysanura, silverfish). Although behaviors of the rove beetles were highly variable by species, i.e., some were carried by ants and some were ignored by ants, the CHC profiles tended to resemble that of the host ants. The generalized scuttle flies Dohrniphora spp. were similar in behavior to each other but the CHC profiles were variable. The legless and wingless scuttle fly Vestigipoda maschwitzi was perfectly integrated into the ant colony as a mimic of ant larvae and also showed CHC profiles common to the ant larvae. The silverfish had very close contact with the ants, but the CHC profiles were quite different from the ants and the quantity itself was very low.